ANALISIS TERHADAP TINDAKAN PENGUASAAN MITRA DI BIDANG PETERNAKAN AYAM: Analysis Of Partners' Controlling Actions In The Field Of Chicken Farming - Syahreza Jakti Kusuma; Anna Maria Tri Anggraini (Reformasi Hukum Trisakti, 2025)
The interpretation of the term “controlling MSMEs” as business partners in a partnership relationship illustrates the application of the control criteria in KPPU Decision No. 21/KPPU-K/2019 and KPPU Decision No. 03/KPPU-K/2021. The research problem in this article is: What is the legal form of control exercised by the reported party in the partnership agreement between PT Sinar Ternak Sejahtera and its partners? This study employs normative legal research with a descriptive approach. The data used consists of primary and secondary data, collected through interviews and various literature sources. The result and conclusions of the study indicate that decision-making within the partnership was unilaterally conducted by PT Sinar Ternak Sejahtera. The decisions also highlight the occurrence of control exerted by large businesses over MSMEs. The criteria for determining control vary across decisions because each decision applies different standards for assessing control and/or ownership. Therefore, KPPU needs to develop guidelines for interpreting the terms “ownership” and/or “control” of medium/large businesses over MSMEs.